Methodology adapted to the formation of F1 hybrids of cacao (Theobroma cacao L.) in Tabasco - Barrón García Yaskara Paulina; Azpeitia Morales, Alfonso; López Andrade Procopio Alejandro; Mirafuentes- Hernández Felipe (Revista Mexicana de Ciencias Agrícolas, 2018)
In Tabasco, the disease “moniliasis” affects the production of cocoa grown by reducing the production of 30% to 100% in plantations. The fungus affects Moniliophthora roreri fruit at any stage of development. In 2006 six resistant “moniliasis” clones joined the genebank in the State of Tabasco. It is necessary to incorporate these character resistance genotypes with high performance and regional adaptation through interbreeding. The aim of this study was to establish a method for the formation of new highly productive Mexican hybrids through controlled pollinations with resistant genotypes. Results of the influence of the container volume and residence time on the inflorescence cocoa for hand- pollination and the percentage of surviving flower after pollination, as well as the influence of hand pollination period are presented in this work, genotypic differences and genetic compatibility. This work has led to 63 different families, offspring of 23 different crosses.